Spatial and temporal distribution of benthic macroinvertebrates in a Southeastern Brazilian river - Silveira,M. P. (2006)
Benthic macroinvertebrate assemblages are structured according to physical and chemical parameters that define microhabitats, including food supply, shelter to escape predators, and other biological parameters that influence reproductive success. The aim of this study is to investigate spatial and temporal distribution of macroinvertebrate assemblages at the Macaé river basin, in Rio de Janeiro state, Southeastern Brazil. According to the "Habitat Assessment Field Data Sheet - High Gradient Streams" (Barbour et al., 1999), the five sampling sites are considered as a reference condition. Despite the differences in hydrological parameters (mean width, depth and discharge) among sites, the physicochemical parameters and functional feeding groups' general structure were similar, except for the less impacted area, which showed more shredders. According to the Detrended Correspondence Analysis based on substrates, there is a clear distinction between pool and riffle assemblages. In fact, the riffle litter substrate had higher taxa in terms of richness and abundance, but the pool litter substrate had the greatest number of exclusive taxa. A Cluster Analysis based on sampling sites data showed that temporal variation was the main factor in structuring macroinvertebrate assemblages in the studied habitats.